2010
DOI: 10.1002/hup.1149
|View full text |Cite
|
Sign up to set email alerts
|

Why do young women smoke? VII COMT as a risk modifying gene for Nicotine dependence – role of gene–gene interaction, personality, and environmental factors

Abstract: Addition of the genetic interaction variable into a model of non-genetic ND predictors [parental smoking, novelty seeking (NS), and lifetime history of trauma], substantially increases the percentage of ND variance explained by the model, as well as the percentage of cases correctly identified by it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
2
6
1
1
Order By: Relevance
“…While this location suggests that this polymorphism has a regulatory function and may affect COMT expression, 65 we found no support for nearby regulatory regions when the ENCODE data were reviewed. Only three studies have reported significant associations between COMT rs9332377 and clinical phenotypes (i.e., hearing loss, 66 suicidal ideation, 67 nicotine dependence 65 ). No studies have evaluated for associations between COMT rs9332377 and fatigue.…”
Section: Discussioncontrasting
confidence: 68%
“…While this location suggests that this polymorphism has a regulatory function and may affect COMT expression, 65 we found no support for nearby regulatory regions when the ENCODE data were reviewed. Only three studies have reported significant associations between COMT rs9332377 and clinical phenotypes (i.e., hearing loss, 66 suicidal ideation, 67 nicotine dependence 65 ). No studies have evaluated for associations between COMT rs9332377 and fatigue.…”
Section: Discussioncontrasting
confidence: 68%
“…Greenbaum et al found smokers with A allele of rs660652 had a higher risk for nicotine dependence, which may result in more difficulty to quit. In contrast, Erlich et al revealed smokers with G allele of rs660652 were more serious of nicotine dependence and less probability of attempts to quit .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mother's lifetime smoking may transmit separate genetic risks than does MSP, since specific genetic factors influence different aspects of smoking independently (Maes et al, 2004). In particular, genetic factors associated smoking initiation (Kendler et al, 1999;Koopmans et al, 1999), risk-taking/disinhibited behavior (Hopfer, Crowley, & Hewitt, 2003;Keyes, Legrand, Iacono, & McGue, 2008), or ND (Greenbaum et al, 2010;O'Loughlin et al, 2004;Weiss et al, 2008) may partially explain the effects of mother's lifetime smoking on adolescent smoking frequency and ND.…”
Section: Discussionmentioning
confidence: 99%